1995
DOI: 10.1006/dbio.1995.1060
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic TGFβ1 Expression in the Secretory Mammary Epithelium Induces Early Senescence of the Epithelial Stem Cell Population

Abstract: An important feature of the mammary gland is the regenerative capacity of its epithelium which is demonstrated upon successive cycles of lactation and involution. Pregnant mice expressing a whey-acidic protein (WAP) promoter-driven transforming growth factor-beta 1 (TGF beta 1) cDNA are unable either to generate a secretory mammary epithelium or to lactate. Here we investigate whether ectopic TGF beta 1 induces this phenotype by affecting the transgenic epithelium directly or in trans. Reciprocal transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
134
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 0 publications
16
134
1
1
Order By: Relevance
“…5 The ratio of apoptotic nuclei (number of apoptotic cells/total number of tumor cells) was significantly higher in transgenic than in non-transgenic tumors: 1.74% vs. 0.93% (265/15,241 vs. 135/14,450; p Ͻ 0.0001, 2 test). This difference is very similar to what has been previously reported in WAP-TGF␤1 glands at multiple stages of development and differentiation; 5 and it is consistent with the conclusion that tumor cells do exhibit a secretory phenotype as suggested by the expression of milk proteins.…”
Section: Morphological Studiesmentioning
confidence: 90%
See 3 more Smart Citations
“…5 The ratio of apoptotic nuclei (number of apoptotic cells/total number of tumor cells) was significantly higher in transgenic than in non-transgenic tumors: 1.74% vs. 0.93% (265/15,241 vs. 135/14,450; p Ͻ 0.0001, 2 test). This difference is very similar to what has been previously reported in WAP-TGF␤1 glands at multiple stages of development and differentiation; 5 and it is consistent with the conclusion that tumor cells do exhibit a secretory phenotype as suggested by the expression of milk proteins.…”
Section: Morphological Studiesmentioning
confidence: 90%
“…Subsequent transplantation studies demonstrated that this phenotype was intrinsic to the transgenic epithelium expressing WAPdriven TGF␤1 and that the effect was cis in nature, i.e., autocrine rather than paracrine. 5 Further analysis of the defect in lobular development in the WAP-TGF␤1 model revealed an increased rate of alveolar cell apoptosis in the transgenic glands. Alveolar cell mitosis, however, also continued at an increased rate over that observed in the normal control glands throughout pregnancy suggesting that autocrine TGF␤1 did not inhibit the proliferation of alveolar mammary epithelial cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SGP-2, for example, is not only induced during mammary gland involution but also during regression of the prostate upon androgenablation and in di erent tumor cell lines induced to undergo apoptosis (Wong et al, 1993(Wong et al, , 1994. Overexpression of TGF-b1 and p53, which are both induced during involution, led to apoptosis of mammary alveolar cells in transgenic mice (Kordon et al, 1995;Li et al, 1996a), pointing towards a functional role of these molecules in involution-associated apoptosis as well. In the mammary glands of WAP-bcl-2 transgenic mice the expression of these genes was not dramatically altered as compared to wildtype mice, indicating that Bcl-2 does not act via modulation of their expression.…”
Section: B B B B B B B B M B Bmentioning
confidence: 99%